O judiciário entre a vontade de poder e o controle remoto judicial: uma resposta hermenêutica - Santos Júnior, Rosivaldo Toscano dos (Universidade do Vale do Rio dos Sinos, 2013)
The study investigates two positions that distort the interpretation of law in Brazil and proposes a solution to solve this problem. Identifies, in both, the decisionism founded on the will to power, breaking up normativity. The idea of the judiciary as a corporation dominates the Supreme Court and the National Council of Justice. They imports institutes that would be the common law. Except that out of context, under the guise of efficiency and in accordance with the will of the market. Are concealed exercise of will power for neglecting the specificity of the case and normativity. Dockets, binding or not, and pseudoprecedents would generate violence against the functional independence of the judges of low courts and against the litigants because the attribution of meaning doesn’t comes the case. In the basis of the judiciary, our study investigates the prevalence of uncritical and obedient to this “Brasilian’s common law”, expressed in dockets and abstract statements. It creates memes. However, our national government history was authoritative and the states interrupts the perception that there is an ontological difference between potestas and potentia – that one can not exist without the other, or without it becoming illegitimate power. Thus, on the basis, the decisionism phenomenon subsists as an extra practice in a learning by observation of summit - modeling, creating or sticking to ad-hoc principles and abstracts concepts. Both vertically (hierarchical - solipsism from supreme court to the basis) and horizontally (on the low courts), it breaks up the autonomy of law, whether in politics and in the economy. “Freedom of the interpreter” as a pretext for libertinism of rules. “Economic efficiency” as disabiliting rules. Erstwhile, speaking on behalf of the casts. Today, neoliberal economic discourse. The economy invades the law, this time in the form of Trojan horse: the Economic Analysis of Law. Replaces up normativity by merchandising utilitarianism. The inauthentic prejudice that sustain this double deformation of hermeneutic born from a operant conditioning (stimulus-reinforcement) of legal practitioners from college to professional activity, and reaching, in particular, its main destination: the judges. This discourse of power produces realities - epistemological ceilings that hide the fact that: a) there is only interpretation in this case because there are no concepts without facticity; b) does not fit the argument from authority beyond normativity; c) the importation of foreign theories must undergo a process of 13 reconciling with our legal, social, political and economic reality. From the ontological-linguistic turn, with the overcoming of the subject-object scheme of the philosophy of consciousness and consideration of the ontological difference (between Being and beings, and text and norm), there is the unveiling of interpretation as existential and the senses will not come from the autonomous subject of modernity, but under intersubjectivity, a truth that comes from the fusion of horizons within a tradition as well as the importance of integrity and coherence of the law. The constitutionally correct answer can not depend on awareness of the judge, the free conviction or from search of the “real truth”. Deciding is not choose, definitely.
Keywords: Teoria da decisão; Hierarquização e solipsismo; Vontade de poder; Neoliberalismo; Resposta constitucionalmente adequada; Theory of decision; Hierarchy and solipsism; The power to will; Neoliberalism; Constitutionally right answer; ACCNPQ::Ciências Sociais Aplicadas::Direito